The linguacultural aspect and semantic index of vocabulary of national clothing of Kazakh people. (Eurasian Journal of Philology Science and Education, 2015)
Due to changes in the social and cultural life of the community, and because of other reasons, some words have become extinct. Therefore, we have got the great scientific interest and a thorough study of words of clothes. Wordswere and are the conductor in history and culture of the people, they open up a broad picture to the researcher, defines the aesthetic tastes and attitudes of the people. Study of linguo-cultural aspect of words definitely is connected with the culture of people. Many scholars have a proof of linguo-cultural approach to the study of words. In fact, we tried this approach through our research. It also describes the role of the notion of language as a nation- culture in the knowledge of people's worldview. And it is through the vocabulary of the Kazakh national dress of the people, which reflects the national heritage and linguistic wealth.
Keywords: language-nation-culture; lexis of clothes; linguaculture; and language worldview